2015
DOI: 10.1007/s00265-015-2016-8
|View full text |Cite
|
Sign up to set email alerts
|

Calling site choice and its impact on call degradation and call attractiveness in the gray treefrog, Hyla versicolor

Abstract: To evaluate the effects of calling site on call degradation, we broadcast synthetic advertisement calls of male gray treefrogs through forest, over open terrain, and across pond water. Calls were recorded at distances of 1, 2, 4, 8, 16, and 32 m. We varied speaker and microphone heights for a total of five elevation combinations ranging from surface level to a height of 1.5 m. We quantified structural degradation in recorded calls using BΔV,^a measure of relative sound energy in call pulses and interpulse inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 101 publications
(175 reference statements)
0
22
0
Order By: Relevance
“…Several anuran species vocalize from positions that maintain the integrity of information contained in acoustic signals along the transmission path (Hödl, ; Schwartz, Hunce, Lentine, & Powers, ) or enhance its intensity (Bailey & Roberts, ; Lardner & bin Lakim, ; Muñoz & Penna, ). Our results indicated that the acoustic structure of calls (pulsed or tonal notes) was the only trait associated with the type of calling site.…”
Section: Discussionmentioning
confidence: 99%
“…Several anuran species vocalize from positions that maintain the integrity of information contained in acoustic signals along the transmission path (Hödl, ; Schwartz, Hunce, Lentine, & Powers, ) or enhance its intensity (Bailey & Roberts, ; Lardner & bin Lakim, ; Muñoz & Penna, ). Our results indicated that the acoustic structure of calls (pulsed or tonal notes) was the only trait associated with the type of calling site.…”
Section: Discussionmentioning
confidence: 99%
“…In our data arboreal calling species were included into the non-aquatic calling site category, and were not analyzed separately because they were mostly present in the family Hylidae, but scarce in Ranidae and Leptodactylidae. Still, we predict arboreal species to have even higher frequency calls relative to aquatic and terrestrial species due to a combination of body size constraints, and favorable transmission of high frequencies from elevated sites (Mathevon et al 1996; Schwartz et al 2016; Cicchino et al 2020). Variation in body size will not only have a direct impact on call frequency due to allometry, but may also limit the possible calling sites a species can occupy, highlighting the relevance of the interaction between morphology and calling site on signal evolution.…”
Section: Discussionmentioning
confidence: 84%
“…Calling at higher perches allows the signal to propagate over larger distances and thereby increases the likelihood of reaching intended receivers (e.g., females, conspecific intruders). This positive relationship between calling-perch height and sound propagation has been shown in insects (Walker and Forrest 1989), birds (Sorjonen 1986), and amphibians (Greer and Wells 1980;Wells and Schwartz 1982;Brenowitz et al 1984;Kime et al 2000;Parris 2002;Kats et al 2012;Schwartz et al 2015). However, animals can also adjust the amplitude of the signal depending on the level of masking abiotic and/or inter-and intraspecific background noise (Lombard 1911;Todt 2002, 2004).…”
Section: Communicated By a Taylor Baughmentioning
confidence: 76%
“…Numerous studies have shown the positive effect of callingperch height on sound propagation on long-and shortdistance communication systems. Sound is attenuated when closer to the ground because of the dense vegetation and ground effect (Marten and Marler 1977;Richard and Wiley 1980;Wells and Schwartz 1982;Forrest 1994;Schwartz et al 2015). In the case of A. femoralis, our results suggest an adjustment to the hypothesis of a general positive effect of calling-perch height on signal effectiveness, where males take advantage of the signal-enhancing effects of calling from high perches without affecting the effectiveness of acoustic spacing with conspecifics.…”
Section: Discussionmentioning
confidence: 99%